Birthplace choices: what are the information needs of women when choosing where to give birth in England? A qualitative study using online and face to face focus groups - Hinton, L; Dumelow, C; Rowe, R; Hollowell, J (BioMed Central, 2017)
Background Current clinical guidelines and national policy in England support offering ‘low risk’ women a choice of birth setting. Options include: home, free-standing midwifery unit (FMU), alongside midwifery unit (AMU) or obstetric unit (OU). This study, which is part of a broader project designed to inform policy on ‘choice’ in relation to childbirth, aimed to provide evidence on UK women’s experiences of choice and decision-making in the period since the publication of the Birthplace findings (2011) and new NICE guidelines (2014). This paper reports on findings relating to women’s information needs when making decisions about where to give birth. Methods A qualitative focus group study including 69 women in the last trimester of pregnancy in England in 2015–16. Seven focus groups were conducted online via a bespoke web portal, and one was face-to-face. To explore different aspects of women’s experience, each group included women with specific characteristics or options; planning a home birth, living in areas with lots of choice, living in areas with limited choice, first time mothers, living close to a FMU, living in opt-out AMU areas, living in socioeconomically disadvantaged areas and planning to give birth in an OU. Focus group transcripts were analysed thematically. Results Women drew on multiple sources when making choices about where to give birth. Sources included; the Internet, friends’ recommendations and experiences, antenatal classes and their own personal experiences. Their midwife was not the main source of information. Women wanted the option to discuss and consider their birth preferences throughout their pregnancy, not at a fixed point. Conclusions Birthplace choice is informed by many factors. Women may encounter fewer overt obstacles to exercising choice than in the past, but women do not consistently receive information about birthplace options from their midwife at a time and in a manner that they find helpful. Introducing options early in pregnancy, but deferring decision-making about birthplace until a woman has had time to consider and explore options and discuss these with her midwife, might facilitate choice.